Regulation of foraging trips and costs of incubation shifts in the Antarctic petrel (Thalassoica antarctica) - Tveraa, Torkild; Lorensten, Svein-Håkon; Sæther, Bernt-Erik (Behavioral Ecology, 1997)
In species where incubation is shared by both parents, the mate's ability to fast on the nest may constrain the time available for foraging. The decision to return to the nest should therefore be a compromise between an animal's own foraging success and its mate's ability to fast on the nest. To examine how the body conditions of incubating Antarctic petrels, Thalassoica antarctica, influence both the length of foraging trips and incubation shifts, we experimentally handicapped females by increasing their flight costs during a foraging trip by adding lead weights to their legs. Handicapped females spent more time at sea and had lower body conditions at arrival to the colony than controls, and, moreover, females in poor body condition at arrival to the colony spent generally more time at sea than those with higher body condition. The prolonged time period spent at sea by handicapped females was associated with higher desertion rates than among controls. The time the incubating mates fasted increased with their body condition at arrival to the colony, suggesting that a high body condition of the incubating bird may reduce the probability of nest desertion. Accordingly, our results suggest that the time spent foraging is adjusted to the body conditions of both the foraging and incubating mate.
Keywords: Dronning Maud Land; fugler; ornitologi; petreller; zoologi; økologi

Seabird research at Svarthamaren during NARE 1996-1997 - Tveraa, Torkild; Røv, Nils; Aanes, Ronny; Jensen, Henrik (Report of the Norwegian Antarctic Research Expedition 1996/97, 1997)
Keywords: Dronning Maud Land; NARE 1996/97; fugler; ornitologi; petreller

Size-Dependent Variation in Reproductive Success of a Long-Lived Seabird, the Antarctic Petrel (Thalassoica Antarctica) - Sæther, Bernt-Erik; Lorentsen, Svein-Håkon; Tveraa, Torkild; Andersen, Reidar; Pedersen, Hans Christian (The Auk, 1997)
We examined how variation in parental quality influences the reproductive success of a long-lived seabird, the Antarctic Petrel (Thalassoica antarctica). In particular, we focused on how quality of parents can interact with and influence the effects of stochastic variation in the environment due to varying climatic conditions. Large annual variation was found in reproductive success. However, body mass of individual chicks at the end and be ginning of the nestling period was strongly correlated in two of the study years, suggesting consistent variation among parents in their ability to feed offspring. Furthermore, chick mass was related both to overall body size and to body mass of their parents. Short brooding-shift intervals also were important for growth and survival of chicks. The probability of chick survival to the age of 30 days (ca. two weeks before fledging) was strongly correlated with chick mass when the chick was left unattended. However, the relative importance of different parental characteristics differed between years. These results show that reproductive success of the Antarctic Petrel is influenced by stochastic variation in the environment, probably re lated to climatic conditions. Effects of this stochastic variation may depend on body mass and/ or body condition of the parents.
Keywords: Dronning Maud Land; NARE 1989/90; NARE 1991/92; NARE 1992/93; fugler; ornitologi; petreller; zoologi